(untitled) (INTEGRATION PROCEEDING, 2023)
Smoking is a social problem that is quite difficult to solve and now it has become a national problem. Siring Menara Pandang is a tourist attraction in Banjarmasin which is located on the outskirts of the river. The place was chosen to interview teenagers who smoked because the place was crowded with visitors. This analysis activity needs to be carried out to obtain an overview of smoking behavior in teenagers so that a health promotion program can be planned to control smoking activity in teenagers. The purpose of this study was to determine the motivation for smoking behavior and to identify smokers in teenagers. The method used in this research is descriptive method using a quantitative approach. The results showed that many of the teenagers who had high motivation in smoking were 54% and the type of cigarette used was filter cigarette, which was 73%. It was concluded that there needs to be attention for today’s teenagers so that they are not addicted to smoking by conducting socialization or education to teenagers.